Pluripotency and X chromosome dynamics revealed in pig pre-gastrulating embryos by single cell analysis - Priscila Ramos-Ibeas (Nature Communications, 2019)
Lineage segregation from conception to gastrulation has been mapped at the single cell level in mouse, human and monkey. Here, the authors provide a comprehensive analysis of porcine preimplantation development using single cell RNA-seq; mapping metabolic changes, X chromosome inactivation and signalling pathways.